On sensitivity of industries and companies to the state of economy - M. S. Konovalova; A. G. Maksimov (Cogent Economics & Finance, 2017)
Cyclicality in industries and companies is scrutinized in the paper. Cyclical industry/firm is that which parameters (in particular, value added by industry and economic value added) have high correlation with the parameter reflecting economic cycles (in particular, GNP). The theoretic approval for the thesis that durable goods industries are more cyclical than nondurable ones is already provided. The aim of the research is to conduct an empirical analysis of cyclicality of Canadian and Russian industries in terms of the aforementioned statement and cyclicality of Russian companies as components of industrial structure. According to the results, the extents of cyclicality of durable and nondurable goods industries in Canada are equal. The theoretical thesis under consideration is correct for the industrial structure of Russia: durable goods industries in Russia are more cyclical than nondurable ones. Moreover, Russian companies also comply with the aforementioned statement. In addition to this, the effect of asymmetrical reaction of industries and companies on expansion and contraction happening in the economy as well as a role of company's management in regulation of the extent of cyclicality of a company are considered in the paper.
Keywords: G10; 330; cyclicality; cyclical industry; cyclical company